An updated and annotated checklist of the lizards of Peninsular Malaysia, Singapore, and their adjacent archipelagos - Grismer, L. Lee; Quah, Evan S. H. (Zootaxa, 2019)
Since the book-formatted, monographic treatment of the lizards of Peninsular Malaysia, Singapore, and their adjacent islands by Grismer (2011), 47 additional species have been added to that fauna bringing the total to 174. One species, Cyrtodactylus stresemanni, was removed from the lizard fauna based on its likely mislabeled type locality; 44 species were described as new—29 gekkonids, 11 scincids, five agamids, and one dibamid; and three others, Cnemaspis narathiwatensis, Cyrtodactylus brevipalmatus, and Scincella melanosticta were recently discovered in northern Peninsular Malaysia. Taxonomic changes for seven previously described species occurring after 2011 are noted and significant, new locality records are documented here for additional species. The intent of this review is to provide an up to date peer-reviewed checklist for the lizard species of this region prior to a pending updated book monograph.